REKONSTRUKSI KONSEP NUSYÛZ DALAM PEMIKIRAN FIKIH FEMINIS KEADILAN - Alamsyah, Alamsyah (Universitas Islam Negeri Raden Intan Lampung, 2018)
The classical fiqh clerics, when defining the word “al-rijâlu qawwâm...” in surah al-Nisa’ verses 34-35, interpreted it as “a husband who becomes a family leader”. From this interpretation, a wife is obliged to obey her husband and the nusyûz act applies only for the wives. In contrast, according to feminist fiqh views, such as Muhammad Syahrûr and Musdah Mulia, Nusyûz is an act of defiance of God’s commands. Therefore hurting the heart of a wife or husband, both through speech and deed, is nusyûz (disobedient). This article compares the views of classical scholars with modern thinkers about the problem of nusyûz in the family. This study concludes that modern thinking is more in line with the principles of equality and justice taught in the Qur’an. Thus, nusyûz can not only happen to the wife but also can be applied to the husband.